Analysis Of Supply Chain Performance And Value Added Of Robusta Coffee At PT. Bondowoso Coffee Distributor - Ramadhani, Shinta Artamevia; Wardhana, Danu Indra; Nalawati, Ara Nugrahayu (International Applied Science, 2024)
A supply chain is the interrelationship between the flow of materials or services, the flow of money, and the flow of information from suppliers, manufacturers, distributors, warehouses, retailers, and end customers. PT Bondowoso Coffee Distributor is one of the agro-industrial PTs engaged in the coffee sector located in Bondowoso district. So far, PT Bondowoso Coffee Distributor, which has a fairly large supply chain, has never measured supply chain performance. Of course, one of the impacts of activities in the supply chain is the addition of product value to robusta coffee. The amount of balanced added value greatly affects the sustainability of a supply chain activity, so it is very beneficial for all actors in the coffee agro-industry supply chain. So the objectives of this research are to analyze the robusta coffee supply chain structure at PT Bondowoso Coffee Distributor, to measure the robusta coffee supply chain performance at PT Bondowoso Coffee Distributor, to analyze the added value of robusta coffee products at PT Bondowoso Coffee Distributor. This research uses the SCOR-AHP and Hayami methods for added value. The results of this research are the robusta coffee supply chain mechanism starts from farmers, collectors, PT Bondowoso Coffee Distributor and costumers. The activities that occur in PT Bondowoso Coffee Distributor are Plan, Source, Make, and Delivery. The performance analysis of PT Bondowoso Coffee Distributor amounted to 85.606 which is included in the average category. Value added of agro-industry from farmers obtained the greatest added value is ground coffee which is 82.22%, the second is roasted coffee at 66.03% and coffee beans at 42.64%. While the value added of agro-industry from collectors obtained the greatest added value is ground coffee at 72.55%, roasted coffee at 40.33% and coffee beans at 35.67%